Math, asked by raisabose2331, 1 year ago

sin^6A+cos^6A = 1 - 3sin^2Acos^2A​

Answers

Answered by avaiiwonderrwomanii
3

sin^6A + cos^6A = (sin²)³ + (cos²)³

= ( sin² + cos² )³ - 3( sin².cos² ) (sin² + cos² )

= 1 - 3sin²cos² × 1

= 1 - 3sin²cos²

Please mark as brainliest !

Answered by panthasaksham77
0

Answer: L.H.S=sin^6a + cos^6a

(sin^2a)^3 + (cos^2a)^3

(sin^2a+cos^2a)^3-3(sin^2a+cos^2a)(sin^2a+cos^2a)

1-3sin^2a+cos^2a*1

1-3sin^2a+cos^2a

Step-by-step explanation:

Hope it helps you!!

Similar questions